Pediatric hepatobiliary disease: Genetic and clinical manifestations - Lien, Nguyen Thi Kim; Anh Hoa, Nguyen Pham; Huy Hoang, Nguyen (Vietnam Journal of Biotechnology, 2021)
In children, hepatobiliary diseases are rarely and mainly due to congenital defects during formation, development of the liver and biliary tract or due to disorders of metabolism. The liver and biliary tract of infant have the incomplete development of physiology during the perinatal until the childhood period. In the process of complete development of the child’s liver and biliary tract, there are important changes and affected by genetic and environmental factors. Therefore, the liver and biliary tract are very vulnerable leading to hepatobiliary diseases in children. Disorders in the formation of bile ducts, bile secretion, hepatocellular metabolism, disturbances of metabolism all lead to the formation associated with hepatobiliary diseases. Based on pathophysiology, the hepatobiliary diseases in children can be divided into two groups: hepatobiliary diseases due to the incomplete development of the structure and function of the liver and biliary tract, and hepatobiliary diseases due to the disruption of metabolic processes in liver cells. The secondary effects of hepatobiliary disease can threaten a child’s life, and is the cause of metabolic disorders such as hypoglycemia, secondary coagulation disorder due to low concentration of vitamin K-dependent factors leading to intracranial hemorrhage in children, infections caused by immunodeficiency, malnutrition, increased portal venous pressure leading to severe gastrointestinal bleeding... Therefore, the hepatobiliary disease in children should be detected and treated early to avoid adverse complications. In the context of this paper, we focus on hepatobiliary diseases with genetic causes in children. Genetic factors and research situation in the World and Vietnam will be also mentioned. The information about genetic and clinical manifestations will be aggregated to contribute to the general understanding of hepatobiliary diseases in children and to orientate the accurate and effective treatment for patients.